PRIMARY MALIGNANT MIXED GERM CELL TUMOR OF THE CONUS MEDULLARIS MASQUERADING AS GESTATIONAL TROPHOBLASTIC NEOPLASIA: A DIAGNOSTIC CHALLENGE (Vietnam Journal of Community Medicine, 2026)
Objective: To report an exceptionally rare case of primary spinal mixed germ cell tumor (GCT) presenting with gynecological symptoms, leading to a significant diagnostic dilemma.Case Presentation: A 29-year-old female presented with abnormal vaginal bleeding and persistent mild elevation of serum βhCG. Despite the absence of intrauterine pathology, she was initially managed for gestational trophoblastic neoplasia (GTN) based on serological markers. The patient underwent multiple courses of chemotherapy for presumed refractory GTN over 16 months. The diagnosis was revisited only after the onset of progressive cauda equina syndrome. Magnetic Resonance Imaging (MRI) revealed an intradural extramedullary tumor at the conus medullaris. Histopathological examination following surgical resection confirmed a malignant mixed GCT. Subsequent multimodal treatment comprising surgery, platinum-based chemotherapy, and radiotherapy resulted in disease control and neurological stabilization.Conclusion: This case highlights a critical diagnostic pitfall where spinal GCTs mimic gynecological malignancies via βhCG secretion. In young patients with unexplained persistent βhCG elevation and negative gynecological imaging, the differential diagnosis must extend beyond gestational pathologies to include extragonadal GCTs. Early consideration of neuro-imaging and expanded tumor marker profiling (αFP) is vital to prevent misdiagnosis and irreversible neurological morbidity.
Keywords: Spinal cord germ cell tumor; Conus medullaris; Gestational trophoblastic neoplasia mimicry; βhCG; Diagnostic pitfall.